Family time : the social organization of care - Folbre, Nancy; Bittman, Michael (Routledge IAFFE advances in feminist economics, 2004)
In this volume, leading experts in analysis of time use from across the globe explore the interface between time use and family policy. They show how social institutions limit the choices that individuals can make about how to divide their time.